Self-Efficacy and Engagement of Islamic Religious Education Students in Online Learning : A Qualitative Approach at Indonesian Higher Education - Hilman Djafar; Ruslan Hasyim; Taqi Ullah Khan (Institut Agama Islam An-Nawawi Purworejo, 2023)
No studies have determined the factors that affected students' engagement and self-efficacy in online learning at Indonesian higher education institutions.